The effect of selenium supplementation on oxidative stress, clinical and physiological symptoms in patients with migraine: a double-blinded randomized clinical trial - Balali, Arghavan; Sadeghi, Omid; Khorvash, Fariborz; Rouhani, Mohammad Hossein; Askari, Gholamreza (Frontiers in Nutrition, 2024)
The present double-blinded randomized clinical trial aimed to investigate the effect of selenium supplementation on oxidative stress, clinical and physiological symptoms in patients with migraine.: In total, 72 migraine patients were randomly assigned to receive either 200 µg/day selenium (n=36) or placebo (n=36) for 12 weeks. Clinical traits of migraine (e.g. severity, frequency, and duration of headaches), mental health indices (e.g. depression, anxiety, and distress), quality of life, biomarkers of oxidative stress (e.g. nitric oxide [NO], malondialdehyde [MDA], total antioxidant capacity [TAC], and total oxidant status [TOS]), and anthropometric indices were assessed at the baseline and end of the study.Results: Selenium supplementation resulted in a significant reduction in NO (-1.24±0.43 vs. 0.16±0.43; P=0.03) levels and a significant increase in TAC (9.89±2.50 vs. -0.18±2.50; P=0.01) compared to the placebo group. Moreover, selenium supplementation had a significant protective effect against MDA levels than placebo (0.33±0.57 vs. 1.83±0.57; P=0.03). In addition, selenium intake was associated with lower headache frequency (-8.15±0.77 vs. -4.12±0.77; P<0.001) and severity (-2.89±0.42 vs. -1.16±0.42; P=0.01) as well as headache impact test 6 (HIT-6) score (-9.22±2.00 vs. -2.08±2.00; P=0.02) compared with controls. For other outcome variables, we found no significant effect.Selenium supplement may be considered as a complementary therapy in patients with migraine due to its beneficial effects on oxidative stress and migraine symptoms. Further studies are needed to affirm our findings.